2019
DOI: 10.1186/s12966-019-0812-7
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial to assess the potential efficacy, feasibility and acceptability of an m-health intervention targeting parents of school aged children to improve the nutritional quality of foods packed in the lunchbox ‘SWAP IT’

Abstract: Background Scalable interventions that improve the nutritional quality of foods in children’s lunchboxes have considerable potential to improve child public health nutrition. This study assessed the potential efficacy, feasibility and acceptability of an m-health intervention, ‘SWAP IT’, to improve the energy and nutritional quality of foods packed in children’s lunchboxes. Methods The study employed a 2X2 factorial cluster randomized-controlled trial design … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
97
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(99 citation statements)
references
References 35 publications
1
97
0
Order By: Relevance
“…This review suggests that nutrition promotion websites and apps can achieve small to moderate changes in fruits, vegetables and nutrient-poor foods and drinks [31-34, 36, 38, 39], albeit with more studies needed to further substantiate their effectiveness. A recent Australian study, which included lunchbox messages provided to parents via a school communication app as part of a multicomponent school-based intervention, found small improvements in the energy intake from recommended foods in the lunchbox [68]. Promisingly, 89% of parents downloaded the app, 71% recalled receiving health promotion messages and most found the messages acceptable and helpful, indicating feasibility and acceptability [68].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This review suggests that nutrition promotion websites and apps can achieve small to moderate changes in fruits, vegetables and nutrient-poor foods and drinks [31-34, 36, 38, 39], albeit with more studies needed to further substantiate their effectiveness. A recent Australian study, which included lunchbox messages provided to parents via a school communication app as part of a multicomponent school-based intervention, found small improvements in the energy intake from recommended foods in the lunchbox [68]. Promisingly, 89% of parents downloaded the app, 71% recalled receiving health promotion messages and most found the messages acceptable and helpful, indicating feasibility and acceptability [68].…”
Section: Discussionmentioning
confidence: 99%
“…A recent Australian study, which included lunchbox messages provided to parents via a school communication app as part of a multicomponent school-based intervention, found small improvements in the energy intake from recommended foods in the lunchbox [68]. Promisingly, 89% of parents downloaded the app, 71% recalled receiving health promotion messages and most found the messages acceptable and helpful, indicating feasibility and acceptability [68]. Digital interventions delivered to parents in other contexts support the use of apps and websites as an effective intervention mode for improving health behaviours.…”
Section: Discussionmentioning
confidence: 99%
“…Educational activities for parents and children are important, but need to be part of a wider package, as information or education for parents on its own is unlikely to make a sustained difference 34. A good example of engaging parents is through the use of social media; one Australian study reported improvements in diet quality of lunchboxes 41. A recent systematic review of interventions to improve quality of packed lunches included 10 programmes mainly from the UK, the USA and Australia.…”
Section: Discussionmentioning
confidence: 99%
“…The program achieved high community awareness (60%) significant reach (e.g. For example, trials conducted by HNELHD staff have identified effective scalable interventions to improve student physical activity, 6,7 and to improve the packing of healthy student lunch-boxes; 8 and effective strategies to improve implementation of dietary guidelines by childcare services 9 and healthy school canteen policies. 3,4 Rigorous controlled evaluations of the service delivery models provided evidence for 'how' community settings could be re-oriented to more effectively deliver obesity prevention services at scale.…”
mentioning
confidence: 99%
“…The capacity of health service staff, built during the demonstration project, has also spawned further innovation. For example, trials conducted by HNELHD staff have identified effective scalable interventions to improve student physical activity, 6,7 and to improve the packing of healthy student lunch-boxes; 8 and effective strategies to improve implementation of dietary guidelines by childcare services 9 and healthy school canteen policies. 10 These successful interventions and implementation support strategies have subsequently been adopted as routine service delivery practice by HNELHD in supporting 420 primary schools and 350 childcare services to promote healthy eating and physical activity.…”
mentioning
confidence: 99%